The relationship between corruption and inequality in Colombia: empirical evidence using panel data for the period 2008-2017 - Sáenz-Castro, Jorge Enrique; García-González, Juan David (Iberoamerican Journal of Development Studies, 2019)
In this paper, we use annual data from 2008 to 2017 for 24 departments of Colombia, including Bogota DC, to study the relationships between Corruption and inequality. The econometric results obtained with the Pedroni methodology (1995, 2001) indicate a positive correlation between corruption and the GINI. This result coincides with the findings of various authors who argue that increases in the level of fraud or low institutional quality result in increased social class inequality. On the other hand, there is a positive and statistically significant relationship between the GINI, unemployment, informality and per capita GDP, while education has a negative impact on income inequality.